Assessing the Doha Round: Market Access, Transactions Costs and Aid for Trade Facilitation - Hoekman, Bernard; Nicita, Alessandro (2012)
This paper compares the predicted trade impacts of a successful Doha Round with the trade effects of actions aimed at reducing domestic trade costs for traders in developing countries and the world as a whole. We show that a relatively small reduction in trade costs will generate trade impacts that are larger than what is likely to emerge even from a relatively ambitious Doha Round market access outcome. This illustrates the importance of complementing market access commitments with measures to reduce trade costs in developing countries--which is the objective of the trade facilitation negotiations in the Doha Round--and additional aid for trade to assist countries in covering the costs of improving trade-related procedures and processes.